Evaluating the quality of planning in new product development projects - Amaral Féris, Marco Antônio; Zwikael, Ofer (Unknown, 2017)
The research and development industry shifts significant resources, from physical products to software. This is triggered by the need to stay competitive in a tough market. However, the poor performance of new product development in the field of software development may restrict this trend. Following a research stream that focuses on NPD planning, we introduce the quality of planning evaluation model (QPEM) and a knowledge base for improving the quality of planning evaluation. QPEM suggests planning quality should be evaluated using two distinct and complementary approaches of top-down and bottom-up for enhancing the accuracy of planning: a) an established measure that assesses 16 planning products and b) a novel measure that assesses 55 factors that affect project performance. This second measure uses cognitive maps, which is a methodology based on expert knowledge that graphically describes the behaviour of a system, and represents the project manager’s know-how and R&D Management Conference 2017, 1 - 5 July 2017, Leuven, Belgium characteristics, technological expertise, top management support, enterprise environmental factors, and the quality of methods and tools in a form that corresponds closely with humans’ perceptions. The alignment between these two approaches is demonstrated through multiple case studies.